An assessment of water resource management approach of Kano River catchment area, Kano State, Nigeria - Salisu, Muhammadu Faruk (Universiti Malaysia Sarawak (UNIMAS), 2015)
The approach of water resource management and development in holistic, integrated manner is referred to as Integrated Water Resource Management (IWRM). It was introduced in the early twentieth century in Spain, France and Italy to cater for hydrographical management through public participation. Nigeria was among those that accepted to implement IWRM process in its water resource management and development. This research investigated the status of Water Resource Management Approach in Kano River catchment Area Kano State Nigeria. Water supply situation in the Kano State remains very poor, despite the efforts of governments for several years. Five million people of the state do not have access to safe, reliable and affordable potable water supplies. The situation led the vulnerable group of the society to get water from alternative sources which are usually very costly, with high labour of fetching water and the water quality may be poor. To address these situations, the State government needs to adopt the IWRM approach in its Water Resource Management and Development. The specific objectives of the study among others were: to identify the status of water resource management approach, identify and determine the strength and weakness of the approach and to recommend to the Kano state government to improve the IWRM process in its water resource management. In an effort to achieve the purpose of the research it employed various methods such as: Documentation of the baseline data of hydrology and meteorology, soil characteristics and water qualities were investigated to enhance the findings of water resources management approach. The questionnaires were used to investigate the aspect of water resource management of the study area. It was validated by logic, experts’ consultation and statistics. 70 respondents from water line ministries and 312 from local communities/ NGO’s through purposive sampling technique. The software of statistical programme of social science, simple statistics was used to analyse the responses received from the key informants. The near end findings validation was conducted with a team of professional water actors in the state. The survey major highlights includes: Majority of respondents, recommends IWRM implementation and it is in the process of development. The State conducts assessment of its water resources. Good coordination exists between water institutions of the State, there is also existence of institutions for conflict resolutions and good rapport exist between local communities with the transboundary and national organisation of water management among others. The shortcoming for IWRM implementation on the other hand includes: The drafted water bill was not sign into law it is awaiting Kano State House of Assembly endorsement, non existence of catchment/ basin water resource management committees, poor stakeholders involvement in the decision making, planning and implementation of water resource development and management, poor dissemination of information to the public on water issues of the State among others. In conclusions it was recommended that the Kano State government to facilitate with immediate effect the water sector bill to be pass into law and its implementation. Subsequently adopts and establish basin/ catchment management committees with membership to be drawn from the local communities, local government authorities and the private sector, as well as non-governmental organisations and women associations. Additionally, model of water resource management was suggested to be entitled, The Participatory Approach of Kano River Water Resource Management. In this model the Kano state was suggest to be demarcated into two river catchment areas: Kano River and Jakara River catchments.